Evaluation of Genetic Parameters for Yield Traits and Stripe Rust Resistance in Bread Wheat Recombinant Inbred Lines: Genetic variability and stripe rust association in bread wheat RILs - Sharma, Renu; Kumar, Satish; Sharma, Indu; Prasad, Pramod; Verma, Ajay; Tiwari, Ratan; Sharma, Pradeep (Journal of Cereal Research, 2025)
Stripe rust, caused by Puccinia striiformis f. sp. tritici, is a significant threat to wheat production worldwide, impacting grain yield, quality, and nutritional value. Therefore, it becomes essential to study the genetic variability among diverse lines. In order to, explore the genetic variability a complete set of RILs (Recombinant inbred lines) derived from cross ‘W8627/PBW343’ was evaluated against stripe rust for seedling and adult plant resistance. This study was conducted at ICAR- Indian Institute of Wheat and Barley Research, Regional Station, Shimla for seedling stage and experimental field of ICAR-IIWBR, Karnal, for adult plant stage during the year 2021-22 and 2022-23. Disease severity and infection type data was recorded and then was used to compute the coefficient of infection (CI) and Area Under Disease Progress Curve (AUDPC). Also, the data for various agromorphological traits was recorded. Significant differences were observed among the RILs after employing analysis of variance across years for all the traits. The combined analysis of variance across years revealed the presence of significant differences for all the traits in RIL population. The correlation analysis displayed the negatively significant association among disease severity and yield contributing traits. The findings revealed extensive genetic variability and high heritability, as well as favorable associations among various traits, facilitating the selection of promising RILs exhibiting disease resistance, elevated yield, and broad adaptability.Keywords: Triticum aestivum, Stripe rust, genetic variability, seedling and adult plant resistance